Preoperative low muscle mass and malnutrition affect the clinical prognosis of locally advanced gastric cancer patients undergoing radical surgery - Zhao, Ailing; Hou, Chong; Li, Yingzi; Liu, Yipin (Frontiers in Oncology, 2023)
Background Gastric cancer is a common and highly aggressive malignant tumor of the gastrointestinal tract that poses a serious threat to human life and health. As the clinical symptoms of early gastric carcinoma are not obvious, many patients are diagnosed in the middle or late stages. With the advancement of medical technology, gastrectomy has become a safer surgical procedure, but it still has a high recurrence and mortality rate after surgery. The prognosis of gastric cancer patients after surgery is not only related to tumor-related factors (i.e., tumor stage) but the patient’s nutritional status. This study aimed to investigate the effect of preoperative muscle mass combined with the prognostic nutritional index (PNI) on clinical prognosis in locally advanced gastric carcinoma. Methods The clinical data of 136 patients with locally advanced gastric carcinoma diagnosed by pathology and undergoing radical gastrectomy were retrospectively reviewed. To analyze the influencing factors of preoperative low muscle mass and its correlation with the prognostic nutritional index. Patients with both low muscle mass and low PNI (≤46.55) were assigned a score of 2, and those with only one or neither of these abnormalities were assigned a score of 1 or 0, respectively, according to the new prognostic score (PNIS). The relationship between PNIS and clinicopathological characteristics was analyzed. Univariate and multivariate analyses were performed to identify risk factors for overall survival (OS). Results Low muscle mass was associated with a lower PNI (P < 0.01). The optimal cut-off value of PNI was 46.55, the sensitivity was 48%, and the specificity was 97.1%. There were 53 (38.97%), 59 (43.38%), and 24 patients (17.65%) in the PNIS 0, 1, and 2 groups, respectively. A higher PNIS and advanced age were independent risk factors for postoperative complications (P < 0.01). The overall survival rate in patients with PNIS 2 score was significantly poorer than in patients with scores of 1 or 0 (3-year OS: 45.8% vs 67.8% vs 92.4%, P < 0.001). A Multivariate Cox hazards analysis showed that PNIS 2, depth of tumor invasion, vascular invasion, and postoperative complications were independent predictors of the poor 3-year survival in patients with locally advanced gastric cancer. Conclusions The combination of muscle mass and the PNI score system can be used to predict the survival outcome of patients with locally advanced gastric cancer.